Safety, tolerability, and immunogenicity of the chimpanzee adenovirus type 3-vectored Marburg virus (cAd3-Marburg) vaccine in healthy adults in the USA: a first-in-human, phase 1, open-label, dose-escalation trial. Issue 10373 (28th January 2023) - Hamer, Melinda J; Houser, Katherine V; Hofstetter, Amelia R; Ortega-Villa, Ana M; Lee, Christine; Preston, Anne; Augustine, Brooke; Andrews, Charla; Yamshchikov, Galina V; Hickman, Somia; Schech, Steven; Hutter, Jack N; et al.
Summary: Background: WHO has identified Marburg virus as an emerging virus requiring urgent vaccine research and development, particularly due to its recent emergence in Ghana. We report results from a first-in-human clinical trial evaluating a replication-deficient recombinant chimpanzee adenovirus type 3 (cAd3)-vectored vaccine encoding a wild-type Marburg virus Angola glycoprotein (cAd3-Marburg) in healthy adults. Methods: We did a first-in-human, phase 1, open-label, dose-escalation trial of the cAd3-Marburg vaccine at the Walter Reed Army Institute of Research Clinical Trials Center in the USA. Healthy adults aged 18–50 years were assigned to receive a single intramuscular dose of cAd3-Marburg vaccine at either 1 × 10 10 or 1 × 10 11 particle units (pu). Primary safety endpoints included reactogenicity assessed for the first 7 days and all adverse events assessed for 28 days after vaccination. Secondary immunogenicity endpoints were assessment of binding antibody responses and T-cell responses against the Marburg virus glycoprotein insert, and assessment of neutralising antibody responses against the cAd3 vector 4 weeks after vaccination. This study is registered with ClinicalTrials.gov, NCT03475056. Findings: Between Oct 9, 2018, and Jan 31, 2019, 40 healthy adults were enrolled and assigned to receive a single intramuscular dose of cAd3-Marburg vaccine at either 1 × 10 10 pu (n=20) or 1 × 10 11 pu (n=20). The cAd3-Marburg vaccine was safe, well tolerated, and immunogenic. All enrolled participants received cAd3-Marburg vaccine, with 37 (93%) participants completing follow-up visits; two (5%) participants moved from the area and one (3%) was lost to follow-up. No serious adverse events related to vaccination occurred. Mild to moderate reactogenicity was observed after vaccination, with symptoms of injection site pain and tenderness (27 [68%] of 40 participants), malaise (18 [45%] of 40 participants), headache (17 [43%] of 40 participants), and myalgia (14 [35%] of 40 participants) most commonly reported. Glycoprotein-specific antibodies were induced in 38 (95%) of 40 participants 4 weeks after vaccination, with geometric mean titres of 421 [95% CI 209–846] in the 1 × 10 10 pu group and 545 [276–1078] in the 1 × 10 11 pu group, and remained significantly elevated at 48 weeks compared with baseline titres (39 [95% CI 13–119] in the 1 ×10 10 pu group and 27 [95–156] in the 1 ×10 11 pu group; both p<0·0001). T-cell responses to the glycoprotein insert and neutralising responses against the cAd3 vector were also increased at 4 weeks after vaccination. Interpretation: This first-in-human trial of this cAd3-Marburg vaccine showed the agent is safe and immunogenic, with a safety profile similar to previously tested cAd3-vectored filovirus vaccines. 95% of participants produced a glycoprotein-specific antibody response at 4 weeks after a single vaccination, which remained in 70% of participants at 48 weeks. These findings represent a crucial step in the development of a vaccine for emergency deployment against a re-emerging pathogen that has recently expanded its reach to new regions. Funding: National Institutes of Health.